PEMBELAJARAN SEKOLAH UNGGULAN DI MASA PANDEMI COVID-19 Studi Tentang Manajemen Pembelajaran di Sekolah Menengah Atas Islam Terpadu Hidayah Klaten - Kelik Wardiyono; Siti Choiriyah; Wasis Pambudi (Jurnal Al-Manar, 2021)
Covid-19 brings implications in various aspects of life for the world community, one of which is education.  Schools in Indonesia "in particular" and the world in general do not apply face-to-face learning to minimize the impacts that will be caused by the global pandemic.  Restricting the crowd, gathering of many people in one place, and adhering to health protocols are imperative.  This study investigates how schools respond to this prolonged policy and condition.  SMAIT Hidayah Klaten is one of the top schools that is seriously affected by the conditions and related policies. The results of the study suggest that SMAIT Hidayah Klaten is very adaptive to government policies regarding the learning process during the Covid-19 period. At least, learning management is carried out by a combination of online and offline learning named “DAR-LING”.  This concept rests on 3 principles, namely online as an ecosystem, school visit and home visit.